Analisis Teknologi Pengolahan Hasil Dan Kelayakan Finansial Cengkeh Di Desa Lelamo, Kecamatan Kulisusu Utara, Kabupaten Buton Utara - Nensiati, Nensiati; Karimuna, La; Herdiansyah, Dhian (Jurnal Sains dan Teknologi Pangan, 2019)
ABSTRACT This study aims to ascertain whether it is financially feasible or not feasible for farmers to process dried clove flowers, wet cloves and clove flower stalks and to find out the processing of clove flower stalks into essential oils. in Lelamo Village, North Kulisusu Subdistrict, North Buton Regency which is still a beginner. The method of determining the sample used in this study is the purposive sampling method. where each farmer counts total costs and variable costs and is deducted by farmers' income from the results of one-year clove penen. The samples were then analyzed qualitatively with income and quantitative analysis methods using the R / C ratio method. The results showed that the processing technology of clove flower stems into essential oils was feasible to be developed with 260 kg of essential oils produced during one harvest period. Where the receipt is Rp. 57,200,000, the total cost is Rp. 4,008,000 and the income is obtained from the income minus the total cost of Rp. 17,120,000. The financial situation of the clove flower processing business produced by the respondent farmers in Lelamo Village, North Kulisusu Subdistrict, North Buton Regency with an average production of dried clove flowers as much as 347.5 kg / year, wet clove 119.6 kg / year, and clove flower stalks as much as 96.4 kg / year. From the calculation results, the total total cost of processing clove flowers for one harvest season is Rp. 6,274,500 / year. Based on the results of the calculation of the financial feasibility analysis of the clove flower business, the R / C ratio of 4.90 is obtained, which is obtained from the average revenue divided by the total cost. For the business of processing dried clove flowers, wet cloves, and clove flower stems financially feasible to develop in terms of the feasibility of the R / C ratio> 1, which is equal to 4.90. Keywords: clove flowers, clove flower stalks, income ABSTRAK Penelitian ini bertujuan untuk memastikan apakah layak atau tidak layak secara finansial pendapatan petani pada pengolahan bunga cengkeh kering, cengkeh basah dan tangkai bunga cengkeh dan untuk mengetahui proses pengolahan tangkai bunga cengkeh menjadi minyak atsiri di Desa Lelamo, Kecamatan Kulisusu Utara, Kabupaten Buton Utara. Metode penentuan sampel yang di gunakan dalam penelitian ini adalah metode purposive sampling, yaitu setiap petani dihitung biaya total dan biaya variabel dan dikurang dengan penerimaan petani dari hasil penen cengkeh selama satu tahun. sampel kemudian dianalisis kualitatif dengan metode analisis pendapatan dan kuantitaf dengan metode R/C ratio, hasil yang diperoleh menunjukan teknologi pengolahan tangkai bunga cengkeh menjadi minyak atsiri layak untuk dikembangkan dengan hasil produksi minyak atsiri sebanyak 260 kg selama satu kali periode musim panen. Dimana penerimaan sebesar Rp 57.200.000, biaya total sebanyak Rp 4.008.000 dan pendapatan diperoleh dari penerimaan dikurang biaya total sebesar Rp 17.120.000. Keadaan finansial dari usaha pengolahan bunga cengkeh yang dihasilkan petani responden di Desa Lelamo Kecamatan Kulisusu Utara Kabupaten Buton Utara dengan rata-rata produksi bunga cengkeh kering sebanyak 347,5 kg/tahun, cengkeh basah 119,6 kg/tahun, dan tangkai bunga cengkeh sebanyak 96,4 kg/tahun. Dari hasil perhitungan J. Sains dan Teknologi Pangan Vol. x, No.x, P. X-X, Th. 2019 2 J. Sains dan Teknologi Pangan (JSTP) 2019 diperoleh besarnya biaya total rata-rata pengolahan bunga cengkeh untuk satu kali musim panen sebesar Rp 6.274.500/tahun. Berdasarkan hasil perhitungan analisis kelayakan finansial usaha pengolahan bunga cengkeh diperoleh nilai R/C ratio sebesar 4,90. Untuk usaha pengolahan bunga cengkeh kering, cengkeh basah, dan tangkai bunga cengkeh secara finansial layak untuk dikembangkan ditinjau dari kelayakan nilai R/C ratio > 1 yaitu sebesar 4,90. Kata kunci :Bunga cengkeh, tangkai bunga cengkeh, pendapatan,